RACHEL CHU’S PERSONAL BRANDING IN KEVIN KWAN’S CRAZY RICH ASIANS: Personal Branding and Motivation - Wafiah Nur Nadifah (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2021)
This thesis is entitled Rachel Chu’s Personal Branding in Kevin Kwan’s Crazy Rich Asians. The objective of the study is to explain Rachel Chu’s personal branding and the motivation of her personal branding. The type of research used is qualitative research. While the approach used is a psychological approach. This research is based on 8 concepts from Peter Montoya, namely specialization, leadership, personality, distinctiveness, visibility, unity, persistence, goodwill. This study shows that Rachel Chu’s does personal branding to improve her quality as an independent woman. Among the eight concepts of personal branding in Peter Montoya’s theory, there are five concepts which are found in Rachel Chu's personal branding. The first concept is specialization. Rachel Chu does personal branding about her strengths, skills, and accomplishments. Rachel Chu focusses on her educational attainment and her qualities. The second concept is personality. Rachel Chu presents herself according to her personality before meeting Nick's family, which means that Rachel Chu has a polite and good personality which is a pure personality without being manipulated. The third concept is distinctiveness. Rachel Chu does personal branding by presenting herself as different from other women. Rachel Chu is not a materialistic person and she is an independent woman. The fourth concept is persistence. Rachel Chu has the determination to achieve something she wants. She does to improve herself and also change herself for the better. The fifth is goodwill. someone who has met Rachel Chu admits that she is an intelligent woman because she is a professor and she is also a graduate of the top university in America. Rachel Chu can speak Mandarin well while she lives in America. Rachel Chu has not forgotten her native culture and she still understands where she comes from. Rachel Chu’s motivation to do personal branding is to pursue her education to improve herself and to be accepted by her boyfriend's family. From the description above, it can be concluded that personal branding in a person is very important. Rachel Chu does personal branding to build her own brand, not someone else's. Branding helps a person to be authentic.